A study on students perception toward plagiarism : bachelor in marketing studies (UMS) / Ili Fizrina Muhamad - Muhamad, Ili Fizrina (2009)
With the development of information and communication technology (ICT), plagiarism becomes an ever more serious problem in the academic community. According to the studies on academic plagiarism conducted at universities in four different European countries, plagiarism rates among students are quite high and students mostly ignore or allow plagiarism because of a lack of knowledge, lack of consequences, or simply because ICT makes plagiarism easy to commit. The findings of the studies presented in this paper indicate that strict policies against plagiarism need to be introduced at universities. In this context, in order to obtain an impression of the marketing students' perceptions, experiences with, and attitudes towards plagiarism, a survey was carried out within the UMS. This report of the survey describing students' perceptions of plagiarism (intentional and unintentional), factor that lead to plagiarism and any correlations found between plagiarism and demographic, situational and perceptual factors. Moreover, it can be concluded that institutions have to be seen to be taking the issue of cheating seriously. At Institute level, there needs to be a review of the policy on academic honesty, linked to definitions of academic impropriety. There also needs to be a clear set of penalties which are designed to discourage involvement in dishonest practice, similarly academics need to be encouraged to follow through suspected transgressions from acceptable practice and supported in the application of the penalty system. Ideally, there should be administrative support to assist academics in the identification of possible sources of material in suspected cases.